2023
DOI: 10.1186/s13071-023-05737-w
|View full text |Cite
|
Sign up to set email alerts
|

Burden of mosquito-borne diseases across rural versus urban areas in Cameroon between 2002 and 2021: prospective for community-oriented vector management approaches

Abstract: Background Over the past two decades, Cameroon has recorded one of the highest rates of urban population growth in sub-Saharan Africa. It is estimated that more than 67% of Cameroon's urban population lives in slums, and the situation is far from improving as these neighbourhoods are growing at an annual rate of 5.5%. However, it is not known how this rapid and uncontrolled urbanization affects vector populations and disease transmission in urban versus rural areas. In this study, we analyse da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…These modifications are important for protein conformation and developmental processes [ 29 , 30 ]. Additionally, O-glycan are required for normal nervous system development and function [ 31 , 32 ], as well as cell-cell communication [ 33 , 34 ]. Given these roles, we investigated the impact of PGANT3 on the hematophagous behavior of Ae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These modifications are important for protein conformation and developmental processes [ 29 , 30 ]. Additionally, O-glycan are required for normal nervous system development and function [ 31 , 32 ], as well as cell-cell communication [ 33 , 34 ]. Given these roles, we investigated the impact of PGANT3 on the hematophagous behavior of Ae.…”
Section: Resultsmentioning
confidence: 99%
“…An accurate and complete genome assembly is essential for understanding the unique aspects of mosquito biology and for developing control strategies to reduce their capacity to spread pathogens [ 31 , 38 ]. Fragmented genome assemblies have historically made it challenging to deeply investigate the biological functions of genes, which is crucial for formulating more effective prevention and control strategies against Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Mosquito bites are more common in rural areas and during the rainy season. It has been reported that many of the mosquito species that involve in disease transmission show a preference for rural areas [11]. However, mosquito bites can also be a problem in urban areas, especially in areas with poor drainage and sanitation [12].…”
Section: Introductionmentioning
confidence: 99%
“…A modeling study indicated that out of an annual number of 390 million dengue virus infections, 96 million result in clinical manifestations [ 17 ]. Another study on the prevalence of dengue revealed that 3.5 billion individuals are at a risk of dengue virus infection [ 18 ]. Species belonging to the genus Culex transmit West Nile virus, St. Louis encephalitis virus, Japanese encephalitis virus, and avian malarial parasites, all of which impose a substantial burden on public health [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%